Aspectos coloidais da adesão de micro-organismos - Araújo, Emiliane Andrade; Andrade, Nélio José de; Carvalho, Antônio Fernandes de; Ramos, Afonso Mota; Silva, Cleuber Antônio de Sá; Silva, Luis Henrique Mendes da (Química Nova, 2010)
The ability of bacteria to attach to surface and develop into a biofilm has been of considerable interest to food industry. Electrostatic, Lifhistz-van der Waals and Lewis acid-base forces are usually considered responsible for the interactions at the interface of the bacterial adhesion. The study of microbial adhesion thermodynamic is important because it represents the reflection of microbial surface and food processing surface physicochemical characteristics. This review examines the most important aspects involved in bacterial attachment to a surface with emphases in thermodynamics of adhesion process.
Keywords: Bacterial adhesion; Biofilm; Microbial surface thermodynamics